Sicknesses, diseases, treatments, and medical costs by socioeconomic variables in Bangladesh - Khan, M. R. (Matiur Rahman), 1938-; Bangladesh Institute of Development Studies (Dhaka : Bangladesh Unnayan Gobeshona Protishthan, 1994)
Covers the period July-Oct. 1987.
Includes statistical tables.
Includes bibliographical references.
Keywords: Medical economics -- Bangladesh -- Statistics; Health care costs -- Bangladesh -- Statistics; Medical care -- Utilization -- Bangladesh -- Statistics; B-21